The Effect of Lithocholic Acid on the Gut-Liver Axis - Sheng, Wei; Ji, Guang; Zhang, Li (Frontiers in Pharmacology, 2022)
Lithocholic acid (LCA) is a monohydroxy bile acid produced by intestinal flora, which has been found to be associated with a variety of hepatic and intestinal diseases. LCA is previously considered to be toxic, however, recent studies revealed that LCA and its derivatives may exert anti-inflammatory and anti-tumor effects under certain conditions. LCA goes through enterohepatic circulation along with other bile acids, here, we mainly discuss the effects of LCA on the gut-liver axis, including the regulation of gut microbiota, intestinal barrier, and relevant nuclear receptors (VDR, PXR) and G protein-coupled receptor 5 in related diseases. In addition, we also find that some natural ingredients are involved in regulating the detoxification and excretion of LCA, and the interaction with LCA also mediates its own biological activity.